Synthesis and characterisation of nanocrystalline ZrN PVD coatings on AISI 430 stainless steel - Taran, A.V.; Garkusha, I.E.; Taran, V.S.; Muratov, R.M.; Skoblo, T.S.; Romaniuk, S.P.; Starikov, V.V.; Baturin, A.A. (Вопросы атомной науки и техники, 2019)
The nanocrystalline films of zirconium nitride have been synthesized using ion-plasma vacuum-arc deposition technique in combination with high-frequency discharge (RF) on AISI 430 stainless steel at 150 °C. Structure examinations X-ray fluorescent analysis (XRF), X-ray diffraction analysis (XRD), scanning electron microscopy (SEM) with microanalysis (EDS), and transmission electron microscopy (TEM), nanoidentation method – were performed to study phase and chemical composition, surface morphology, microstructure and nanohardness of coatings. The developed technology provided low-temperature coatings synthesis, minimized discharge breakdown decreasing formation of macroparticles (MPs) and allowed to deposit ZrN coatings with hardness variation 26.6…31.5 GPa. It was revealed that ZrN single-phase coatings of cubic modification with finecrystalline grains of 20 nm in size were formed. Нанокристалічні плівки нітриду цирконію були синтезовані вакуумно-дуговим методом із застосуванням високочастотного розряду (ВЧ) на поверхні нержавіючої сталі марки AISI 430 при 150 °C. Для вивчення фазового і хімічного складів, морфології поверхні, мікроструктури і нанотвердості покриттів застосовувалися рентгенофлуоресцентний (XRF) та рентгеноструктурний (XRD) аналізи, скануюча електронна мікроскопія (SEM) з мікроаналізом (EDS) та просвічувальна електронна мікроскопія (TEM). Розроблена технологія забезпечує низькотемпературний синтез покриттів, зменшуючи утворення макрочасток, а також дозволяє осаджувати покриття ZrN з твердістю 26,6…31,5 ГПа. Встановлено утворення однофазних полікристалічних плівок ZrN кубічної модифікації з розміром зерен 20 нм. Нанокристаллические пленки нитрида циркония были синтезированы вакуумно-дуговым методом с применением высокочастотного разряда (ВЧ) на поверхности нержавеющей стали марки AISI 430 при 150 °C. Для изучения фазового и химического составов, морфологии поверхности, микроструктуры и нанотвердости покрытий применялись рентгенофлуоресцентный (XRF) и рентгеноструктурный (XRD) анализы, сканирующая электронная микроскопия (SEM) с микроанализом (EDS) и просвечивающая электронная микроскопия (TEM). Разработанная технология обеспечивает низкотемпературный синтез покрытий, уменьшая образование макрочастиц, а также позволяет осаждать покрытия ZrN с твердостью 26,6…31,5 ГПа. Установлено образование однофазных поликристаллических пленок ZrN кубической модификации с размером зерен 20 нм.